Writing for museums - Wallace, Margot A. 1941- (Rowman & Littlefield, 2014)
"Whether written by administrators, staffers, freelancers, or interns, words are delivered by people in your museums with the knowledge, to be interpreted by strangers. Your story is told everywhere, and with each narration it reinforces your brand; hopefully every single word reflects your brand. If you ever wished for a good writer, right on staff, ready to take on project, major or routine, here's the help you're looking for. Writing for Museums will help all staff who write better--and result in clearer communication with and education for--all your visitors"--Provided by publisher.